Denda Adat pada Tradisi Pepadun Masyarakat Lampung dalam Perspektif Hukum Islam - Tri Wahyuni; Inni Inayati Istiana; Ratna Asmarani (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
The people of Lampung, who are predominantly moslem, have a form of implementing customary fines known as dau. There is the term cepala or cepalau, which means 'violation of customary law' in Lampung, which is generally based on Islamic law. The people of Lampung, especially the Pepadun custom in West Tulangbawang Regency, adhere to customary law, which is a reflection of self-esteem that is relevant to the culture of the archipelago. This article aims to find out the practice of "customary fines' among the people of Lampung Pepadun in West Tulangbawang and describe the Islamic perspective on the practice of these customary fines. The researcher used the elicitation method with observing, note-taking, and interviewing techniques within the framework of legal anthropological theory with a phenomenological approach. In general, the practice of dau is in line with Islamic law. There is a stipulation of dau on the types of violations of customary law at mild, moderate, and serious levels, which have consequences of dau and social sanctions. In addition, there are types of violations of customary law in general that only result in punishment without social sanctions. The determination of dau is intended as social control to maintain order among the Pepadun indigenous people.